Role of Distributed Optical Fiber Sensors for FPGA Based implementation of pulse coding technique –An overview - Mulualem, Yelkal; Sirajudeen, M.Mohamed (IJRDO -Journal of Computer Science Engineering, 2015)
Over the last few years fiber sensing technology has been rapidly progressing for a wide range of industrialapplications in strategic sectors such as energy, transportation and security, also including civil and structuralengineering, geothermal and environmental monitoring. Advanced control electronics play a key role in suchdevelopments, allowing for significant performance improvement in the sensor systems. In this research paperto discuss the role of distributed optical fiber sensors in the implementation of FBGA based implementation ofpulse coding technique. The proposed technique allows for a significant signal to noise ratio enhancement andconsequent sensing range extension, allowing for temperature measurement over several tens of kilometres withmeter scale spatial resolution